2022
DOI: 10.1111/zph.12907
|View full text |Cite
|
Sign up to set email alerts
|

Survey of SARS‐CoV‐2 in dogs and cats in high‐risk areas during the second wave of COVID‐19 outbreak, Thailand

Abstract: Summary A cross‐sectional survey of SARS‐CoV‐2 in domestic dogs and cats was conducted in high‐risk areas, five subdistricts of Samut Sakhon Province, the epicenter of the second wave of the COVID‐19 outbreak in Thailand in February 2021. A total of 523 swab samples (nasal, oral, and rectal swabs) and 159 serum samples from dogs (n = 83) and cats (n = 93) were collected and tested for SARS‐CoV‐2 RNA and antibodies. All swab samples tested negative for SARS‐CoV‐2 RNA by real‐time RT‐PCR with three panels of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
5
16
0
Order By: Relevance
“…The rate of susceptibility to each VOC in pets could not be determined from this study due to passive sampling; however, the Alpha VOC was relatively more prevalent in this investigation due to its endemicity in kenneled cats of scenario A, even though these infected cases were sampled during the fourth wave of the COVID-19 outbreak in Thailand when the Delta VOC (B.1.617.2) was predominant ( 32 ). Remarkably, the presence of SARS-CoV-2 could be related to the sampling time, the health condition of infected pets, and contact between pets and owners, as indicated by previous studies ( 10 , 33 ). In accordance with the results of several studies ( 34 , 35 ), we found that infected pets were cared for by SARS-CoV-2-infected owners residing in close contact with their pets, becoming prone to human-to-animal transmission.…”
Section: Discussionsupporting
confidence: 56%
“…The rate of susceptibility to each VOC in pets could not be determined from this study due to passive sampling; however, the Alpha VOC was relatively more prevalent in this investigation due to its endemicity in kenneled cats of scenario A, even though these infected cases were sampled during the fourth wave of the COVID-19 outbreak in Thailand when the Delta VOC (B.1.617.2) was predominant ( 32 ). Remarkably, the presence of SARS-CoV-2 could be related to the sampling time, the health condition of infected pets, and contact between pets and owners, as indicated by previous studies ( 10 , 33 ). In accordance with the results of several studies ( 34 , 35 ), we found that infected pets were cared for by SARS-CoV-2-infected owners residing in close contact with their pets, becoming prone to human-to-animal transmission.…”
Section: Discussionsupporting
confidence: 56%
“…Earlier during the pandemic, more precisely between June 2020 and February 2021, seroprevalence levels ranging from 1 to 2% were found in dogs and cats in Poland [ 26 ]. Such relatively low proportions of seropositive animals (between 0.2% and 6%) have been similarly observed during that time in different countries globally [ 12 , 20 , 21 , 22 , 23 ] and mirrored the situation in the human population. However, as the pandemic progressed and sharp increases in the number of cases were seen in humans worldwide, higher seroprevalences were also observed in companion animals.…”
Section: Discussionsupporting
confidence: 53%
“…Apart from mink and white-tailed deer, SARS-CoV-2 cases have been reported in dogs and cats, among others. Although there have been a number of articles on the seroprevalence of SARS-CoV-2 in companion animals, there are still many unknowns (e.g., regarding their susceptibility to newly emerging VOCs), and the results of the studies vary considerably depending on sample collection time and location [ 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…During investigation period, we identified SARS-CoV-2 delta variant of concern (B.1.617.2) in dogs and cats with the occurrence of 20.0% (1/5) in dogs and 7.1% (1/14) in cats (16.7%; 2 from 12 COVID-19 households). Notably, the occurrence of SARS-CoV-2 may relate to timing of sample collection, health condition of animals and close contact with the owners 1 , 22 , 23 . The B.1.617.2 lineage was a predominant lineage of the recent 4th wave of COVID-19 outbreaks in Thailand 13 .…”
Section: Discussionmentioning
confidence: 99%